Job stress and post-retirement health in the Hertfordshire Cohort Study. (27th September 2018) - Walker-Bone, K; D'Angelo, S; Stevens, M; Linaker, C; Dennison, E; Cooper, C; Syddall, H
Abstract: Background: Job demand–control (DC) and effort–reward imbalance (ERI) are two commonly used measures of work stress which are independently associated with health. Aims: To test the hypothesis that DC and ERI have different and cumulative effects on health. Methods: DC and ERI were assessed in the Hertfordshire Cohort Study. The characteristics and occupations of men and women reporting either or both work stresses were compared and the interaction of these with health status were explored. Results: Complete data were available for 1021 men and 753 women, reporting on their most recent or current job. A total of 647 (63%) men and 444 (59%) women reported neither work stress, while 103 (10%) men and 78 (10%) women reported both. Patterns of ERI and DC, alone and in combination, were different by type of occupation and by gender. Men reporting both work stresses (as compared with neither) were more likely to be single. Reported ERI with DC in the most recent or current job was associated with: poorer SF-36 physical function scores (OR 2.3 [95% CI 1.5–3.7] for men; OR 2.0 [95% CI 1.2–3.6] for women) and mental health scores (OR 2.8 [95% CI 1.8–4.4] for men; OR 3.1 [95% CI 1.8–5.3] for women). Moreover, average grip strength was 1.7 kg (95% CI 0.2–3.3) lower among men who described both work stresses. Conclusion: DC and ERI are two models of the psychosocial workplace environment which offer different but cumulative insight into the impacts of work on an individual's psychological and physical health, particularly in a population sample.